Beauty Influencer Impact on Late Gen Z's Skincare Purchase at UNAIR and MSU: A Cross-Sectional Study - Tanujaya, Angeline Felisca; Sabariman, Jevon Samuel; Sasmita , Anggininda Salsabila Dwi; Binti Gulam Manaver, Asamah Nurul Huda; Setijawan, Danella Athaillah Putri; Nayyara, Danish Aulia Siti; Husada, Fathur Rahman Digda Putra; Razali, Nur Aina Farhah; Abd Aziz, Nur Izzah; Nurul Nikmah; Binti Hasbullah, Rabiatul Adawiyah; Gesnita Nugraheni; Elida Zairina (Jurnal Farmasi Komunitas, 2025)
The increasing popularity of skincare products among late Gen Z is heavily influenced by beauty influencers, especially on social media platforms such as TikTok and Instagram. While credibility is considered a crucial factor in purchase decisions, emerging trends suggest that popularity and ability to entertain may play stronger roles. This study aimed to analyze the impact of beauty influencers on skincare purchasing decisions among late Gen Z students at Universitas Airlangga (UNAIR) and Management and Science University (MSU). A cross-sectional survey was conducted using accidental sampling and involved 115 students (UNAIR n=58, MSU n=57) aged 18-23 from non-health faculties, sampled at the area of Campus B using Spearman’s rank correlation to assess the relationship between influencer attributes (credibility, ability to entertain, trend and popularity) with purchase intention. The findings indicate a moderate and significant correlation between beauty influencer attributes and consumer purchase intention (r = 0.604, p < 0.001). Among the independent variables, popularity (r = 0.585) and trend (r = 0.540) showed the strongest correlations with purchase intention, while credibility (r = 0.329) showed the weakest correlation. This suggests that late Gen Z consumers prioritize an influencer's popularity relevance over credibility, highlighting how beauty influencer shape skincare purchasing behaviour and offering it more ethical marketing and informed consumer decisions.